HIV-1 viral protein R (Vpr) induces fatty liver in mice via LXRα and PPARα dysregulation: implications for HIV-specific pathogenesis of NAFLD - Agarwal, Neeti; Iyer, Dinakar; Gabbi, Chiara; Saha, Pradip; Patel, Sanjeet G; Mo, Qianxing; Chang, Benny; Goswami, Biman; Schubert, Ulrich; Kopp, Jeffrey B.; Lewis, Dorothy E; Balasubramanyam, Ashok (Scientific Reports, 2017)
HIV patients develop hepatic steatosis. We investigated hepatic steatosis in transgenic mice expressing the HIV-1 accessory protein Vpr (Vpr-Tg) in liver and adipose tissues, and WT mice infused with synthetic Vpr. Vpr-Tg mice developed increased liver triglyceride content and elevated ALT, bilirubin and alkaline phosphatase due to three hepatic defects: 1.6-fold accelerated de novo lipogenesis (DNL), 45% slower fatty acid ß-oxidation, and 40% decreased VLDL-triglyceride export. Accelerated hepatic DNL was due to coactivation by Vpr of liver X receptor-α (LXRα) with increased expression of its lipogenic targets Srebp1c, Chrebp, Lpk, Dgat, Fasn and Scd1, and intranuclear SREBP1c and ChREBP. Vpr enhanced association of LXRα with Lxrα and Srebp1c promoters, increased LXRE-LXRα binding, and broadly altered hepatic expression of LXRα-regulated lipid metabolic genes. Diminished hepatic fatty acid ß-oxidation was associated with decreased mRNA expression of Pparα and its targets Cpt1, Aox, Lcad, Ehhadh, Hsd10 and Acaa2, and blunted VLDL export with decreased expression of Mttp and its product microsomal triglyceride transfer protein. With our previous findings that Vpr circulates in HIV patients (including those with undetectable plasma HIV-1 RNA), co-regulates the glucocorticoid receptor and PPARγ and transduces hepatocytes, these data indicate a potential role for Vpr in HIV-associated fatty liver disease.
EVALuna2:35296